2012
DOI: 10.4103/0974-9233.102743
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the rate of regression after conductive keratoplasty with or without prior laser-assisted in situ keratomileusis or photorefractive keratectomy

Abstract: Purpose:To assess the regression rate of conductive keratoplasty (CK) in patients with or without previous laser-assisted in situ keratomileusis (LASIK) or photorefractive keratectomy (PRK).Setting:University of Utah, Medical School, John A. Moran Eye Center, Salt Lake City, Utah.Materials and Methods:A retrospective, age-matched chart review identified records of 6 patients who underwent CK after refractive surgery and 12 patients who underwent CK without prior refractive surgery. The main outcome measures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
(11 reference statements)
1
7
0
Order By: Relevance
“… 17 Moshirfar et al also suggested that SMILE surgery could offer good predictability and safety. 24 Our results are comparable with these previously published studies, and these investigations together suggest that the SMILE procedure shows high predictability in both groups, even in the long term.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 17 Moshirfar et al also suggested that SMILE surgery could offer good predictability and safety. 24 Our results are comparable with these previously published studies, and these investigations together suggest that the SMILE procedure shows high predictability in both groups, even in the long term.…”
Section: Discussionsupporting
confidence: 92%
“… 23 These cells may transform to myofibroblast cells and contract during the wound healing process and contribute to the steepening of the cornea. 22 24 Another possible reason for the regression may be the epithelial hyperplasia, which also correlated positively with the degree of myopia. 25 26 Ganesh et al found a significant epithelial thickness increase in the central and superior zones in the high myopic eyes.…”
Section: Discussionmentioning
confidence: 99%
“… 181 The main goal of this method is to maintain the results and refractive stability with cross-linking, but it seems that corneal collagen cross-linking is effective for preventing regression 181 and more studies are needed in this regard. Regression is one of the major complications of CK, either alone or combined with other methods, and it can be related to the degree of corneal irregularity and the degree of refractive error that causes unstable and unpredictable results 168 , 180 , 182 , 183 and it seems to occur more commonly in younger people. 184 Also, in the first few days after surgery, patients complained of foreign body sensation and light sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…Conductive keratoplasty as an ancillary enhancement technique can be used for myopic overcorrection 83 and hyperopic undercorrection. 84 However, important issues related to initial overcorrection, delayed onset of refractive stability, regression, and lack of an established nomogram detract from consistent use of this technique.…”
Section: Lasik Enhancement/moshirfar Et Almentioning
confidence: 99%